The Influence Of Subtitled Movies On Students Vocabulary Mastery - Abu Bakar; Sayid Ma'rifatullah (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2023)
The purpose of this study was to examine the influence of English Subtitle Movie on the vocabulary mastery achievement of Junior High School students. The resecher used a quasi-experimental design with nonrandomized experiment and control group design. To conduct the research, the researcher used Junior High School students and divided into two groups, experimental and control class, at SMPN 2 Gudo. Data were collected using two instruments: pre/post tests, both of which were made by researchers. The data obtained from the test were analyzed using an independent sample t-test. The results were analyzed by testing the effect of English Subtitle Movie on students' vocabulary mastery. The results of this study indicate that the implementation of English Subtitle Movie used in this study has a significant influence on students' language achievement in vocabulary mastery.